Letters and notes on the manners, customs, and condition of the North American Indians - Catlin, George, 1796-1872. (Minneapolis)
2 cilt (1. c. viii, 264 sayfa, [4] sayfa indeks ; 2. c. viii, 266 sayfa, [10] sayfa indeks)